Bulgaria : Selected Issues. (IMF Staff Country Reports; Country Report, 2010)
Bulgaria's potential output growth in future could be markedly lower, and it may take considerable time for the excess labor and resources to be absorbed by other sectors, in particular by the export sector. This suggests that the natural level of rate of unemployment will rise and remain higher, and the full employment level is likely to decline. There is a requirement of significant improvements in labor productivity and competitiveness, as well as reforms to further improve labor mobility and participation.